RATIO DECIDENDI YANG DIBERIKAN HAKIM PADA PUTUSAN NIET ONVANKELIJKE VERKLAARD (TIDAK DAPAT DITERIMA) DALAM PERKARA MEREK GKRI: Decidendi Ratio Given By Judge In The Verdict of “Niet Ontvankelijk Verklaard” Case Ruling of The Trademark of The GKRI - Sifra Zifora; Ning Adiasih (Faculty of Law, Universitas Trisakti, 2025)
A NO (Niet Ontvankelijk Verklaard) verdict is caused by a formal defect in a lawsuit or the non-fulfillment of formal requirements and often occurs at the exception stage. If the formal requirements are unmet, the final decision will be impacted. So the formulation of the problem in this study is what is the ratio of decidences used by the judge in giving the NO Decision in the GKRI Trademark case. To answer this research, normative research is carried out which is descriptive analysis by sourcing secondary data, which is analyzed qualitatively, while conclusions using a deductive approach. The conclusion and the result of this study is that the judge granted the exception of the Defendant on the basis that the Plaintiff does not have legal standing to apply for trademark cancellation under Law Number 20 Year 2016, so the verdict of Unacceptable/NO is not appropriate, because trademark cancellation can be done by any interested party. In this case, the Plaintiff fulfills the formal requirements of filing a lawsuit, so it has no reason to be sentenced to NO.